Party of one : the rise of Xi Jinping and China's superpower future - Wong, Chun Han (Avid Reader Press, 2023)
"Party of One shatters the many myths and caricatures that shroud one of the world's most secretive political organizations and its leader. Many observers misread Xi during his early years in power, projecting their own hopes that he would steer China toward more political openness, rule of law, and pro-market economics. Having masked his beliefs while climbing the party hierarchy, Xi has centralized decision-making powers, encouraged a cult of personality around himself, and moved toward indefinite rule by scrapping presidential term limits-stirring fears of a return to a Mao-style dictatorship. Today, the party of Xi favors political zeal over technical expertise, trumpets its faith in Marxism, and proclaims its reach into every corner of Chinese society with Xi portraits and hammer-and-sickle logos. Under Xi, China has challenged Western preeminence in global affairs and cast its authoritarian system as a model of governance worthy of international emulation. As a China reporter for the Wall Street Journal, Chun Han Wong has chronicled Xi Jinping's hard-line strategy for crushing dissent against his strongman rule, his political repression in Hong Kong and Xinjiang, and his increasingly coercive efforts to reel in the island democracy of Taiwan, as well as the domestic and diplomatic fallout from the Covid-19 pandemic. When the Chinese government refused to renew Wong's press credentials and forced him to leave mainland China in 2019, he moved to Hong Kong to continue covering Chinese politics and its autocratic turn under Xi. Now, Wong has drawn on his years of firsthand reporting across China-including conversations with party insiders, insights from scholars and diplomats, and analyses of official speeches and documents-to create a lucid and historically rooted account of China's leader and how he inspires fear and fervor in his party, his nation, and beyond"--